Characterization of Myostatin (MSTN) Gene Using PCR-RFLP Method in KUB Chicken - M. F. Sugara; D. Depison; G. Gushairiyanto (Universitas Bengkulu, 2023)
This study aims to obtain MSTN gene diversity and MSTN gene association. The materials used in this study were 96 KUB chickens and 96 KUB chicken blood samples consisting of 41 males and 55 females. This research method is an experiment. Data collected included body weight, weight gain and body size of male and female KUB chickens, and diversity and association of MSTN genes. Data analysis used mean difference test (T-test), T2-Hotelling, Principal Component Analysis (PCA), Genotype and allele frequencies, Hardy-Weinberg equilibrium, Heterozygosity and Polymorphic Information Content (PIC). The results showed that body weight at 1 and 2 months of age, body weight gain at 1-2 months and body size of male KUB chickens at two months were significantly (P<0.05) higher than female KUB chickens. The body size characteristic of male and female KUB chickens is chest circumference (CC) while the body shape characteristic is wing length (WL). The MSTN|MspI gene in KUB chickens is polymorphic. The KUB chicken population is in Hardy-Weinberg imbalance. Heterozygosity of the KUB chicken population showed a value of Ho (0.31) < He (0.51). The MSTN| MspI gene of KUB chicken was associated with body weight, weight gain and body measurements and the best genotype was (-/-).